PENGARUH KEGIATAN EKSTRAKURIKULER SOFTBALL TERHADAP KEBUGARAN JASMANI SISWA SMAN 2 CIMAHI - Rahmat Zulkhomis, - (2012)
The purpose of this study is to reveal the influence of extracurricular activities for physical fitness softball SMAN 2 Cimahi. The method used in this study is a pretest-posttest experimental method design, the study population are students of SMAN 2 Cimahi then students sampled were 26 male students (11 students in grade 1, 8 grade 2 students and 7 students grade 3) are all taken. Based on the data processing and analysis of test results by using the program SPSS 20.0 for windows. For the first hypothesis on one class with a p value (sprint 60 m = 0001, pull-ups = 0003, sit-ups = 0000, vertical jump and ran 1000m = 0003 = 0013) ≤ 00:05 the first hypothesis is proved that "There is a growing Physical Fitness grader significant overall through extracurricular activities a softball game at SMAN 2 Cimahi ". It's been proven; For the second hypothesis in the second grade with a p value (sprint 60 m = 0006, pull-ups = 0014, sit-ups = 0002, vertical jump and ran 1000m = 0007 = 0004) ≤ 00:05 the second hypothesis is proved that "there Physical Fitness increased significantly sophomore through extracurricular activities a softball game at SMAN 2 Cimahi ". It's been proven; For the third hypothesis in the third grade with a p value (sprint 60 m = 0077, pull-ups = 0045, sit-ups = 0017, vertical jump and ran 1000m = 0006 = 0008) ≤ 00:05 the third hypothesis is proved that "there Physical Fitness-class students increased significantly over the three-game softball extracurricular activities at SMAN 2 Cimahi ". Been proven. Multi-variat test (MANOVA) (p ≤ 0.05) is used for the fourth hypothesis with p value (sprint 60 m = 0801, pull-ups = 0260, sit-ups = 0687, vertical jump and ran 1000m = 0880 = 0959) ≤ 0:05 the fourth hypothesis "There are significant differences regarding the level of physical fitness among students in grade 1, 2 and 3 through extracurricular activities a softball game at SMAN 2 Cimahi" not proven. So the conclusion is an extracurricular activity to give softball a significant effect on physical fitness of students of SMAN 2 Cimahi. To the authors suggest to the coaches and trainers to maintain and improve softball extracurricular activities to develop students' physical fitness.